2006
DOI: 10.1016/j.combustflame.2006.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Flame height measurement of laminar inverse diffusion flames

Abstract: Flame heights of co-flowing cylindrical ethylene-air and methane-air laminar inverse diffusion flames were measured. The luminous flame height was found to be longer than the height of the reaction zone determined by planar laser-induced fluorescence (PLIF) of hydroxyl radicals (OH) because of luminous soot above the reaction zone. However, the location of the peak luminous signals along the centerline agreed very well with the OH flame height. Flame height predictions using Roper's analysis for circular port … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 24 publications
1
75
0
Order By: Relevance
“…Previous investigations on laminar air flames already found structurally similar flames for IDF and NDF [4,8]. However, when differential diffusion was strong, differences between IDF and NDF start to emerge, e.g.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous investigations on laminar air flames already found structurally similar flames for IDF and NDF [4,8]. However, when differential diffusion was strong, differences between IDF and NDF start to emerge, e.g.…”
Section: Resultsmentioning
confidence: 91%
“…Whilst some studies of laminar air flames have found that inverse and normal diffusion flames are similar in structure [4,8], other authors have observed differences in the measured temperature in air combustion [7] and in the OH* chemiluminescence fields in oxy-fuel combustion [9]. To our knowledge, a similar comparison of turbulent normal and inverse diffusion flames has not been published.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The structure and soot formation characteristics of coflow laminar normal diffusion flames (NDF) (fuel jet is issued into air) have been experimentally investigated by many researchers, e.g., Mitchell et al [7], Santoro and co-workers [8], Faeth and co-workers [9], among many others, and numerically studied using relatively detailed chemistry by Kaplan and Kailasanath [10], Smooke et al [11,12], and Guo et al [13], among others. Coflow inverse diffusion flames (IDF) have also been investigated experimentally by various researchers [14][15][16][17][18][19]. It has been made clear that IDFs exhibit remarkably different soot formation features from those of NDFs due to the very different temperature, chemical environment, and residence time experienced by incepted soot particles [10].…”
Section: Introductionmentioning
confidence: 99%